2017
DOI: 10.3168/jds.2016-11401
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial on the effects of a free-access acidified milk replacer feeding program on the health and growth of dairy replacement heifers and veal calves

Abstract: The objectives of this study were to evaluate the effects of free-access acidified milk replacer feeding on the pre- and postweaning health of dairy and veal calves. Individually housed calves were systematically assigned at birth to 1 of 2 feeding programs: free-access feeding (ad libitum) of acidified milk replacer (ACD, n=249) or traditional restricted feeding (3L fed twice daily) of milk replacer (RES, n=249). Calves were fed milk replacer containing 24% crude protein and 18% fat. Acidified milk replacer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
4
27
0
7
Order By: Relevance
“…Source of the calves had an influence on the growth of calves. Colostrum management and plane of nutrition are critical components of early life management on source dairy farms that influence the health and productivity of calves (Faber et al, 2005;Windeyer et al, 2014;Todd et al, 2017). As the management of these factors vary depending on the source dairy farm of origin (Renaud et al, 2017), this could explain some of the variation present with regard to the different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Source of the calves had an influence on the growth of calves. Colostrum management and plane of nutrition are critical components of early life management on source dairy farms that influence the health and productivity of calves (Faber et al, 2005;Windeyer et al, 2014;Todd et al, 2017). As the management of these factors vary depending on the source dairy farm of origin (Renaud et al, 2017), this could explain some of the variation present with regard to the different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Improved energy status protects against disease and supports immune function (Todd et al, 2017). It has been reported that 17% of surveyed Canadian dairy source farms providing inferior nutrition to male calves compared with female calves (Renaud et al, 2017), and this, combined with the energy expenditure and mobilization occurring during calf transport (Knowles et al, 1999), means that many male calves enter the veal industry with suboptimal energy status and low body fat cover (Wilson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that the feed intake and average daily gain (ADG) of calves fed acidified MR was not different from that of calves fed normal MR when there was no difference in intake and milk composition [4][5][6]. Woodford [7] reported that feeding calves acidified MR ad libitum did not improve the digestion and absorption of nutrients.…”
Section: Introductionmentioning
confidence: 99%